KINERJA KEUANGAN LAYANAN KESEHATAN SEBELUM DAN SESUDAH PENERAPAN PPK BLU - Ratna Suryaningsih (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2015)
This study aimed to analyze the differences in performance of financial ratios Dr. Soeradji Tirtonegoro hospital before and after application of “Pola Pengelolaan Keuangan Badan Layanan Umum” / PPK BLU. The ratio is based on conscientious Director General of Treasury Regulation No. Per-36/PB/2012 .The data used in this study were obtained from financial ratios of Dr. Soeradji Tirtonegoro hospital during the period 2002-2012. This study examines the financial performance consisted of Cash Ratio, Current Ratio, Collection Period, Fixed asset turnover, Return on assets and Return on equity. While the performance of services in representing the growth of competitiveness in proksikan by Sales Growth (SALG) and Activity Growth. Processing of the data in this study performed using a statistical technique Uji Beda T-test dengan Related Samples or paired samples often diistilakan with t-test .The findings of this study indicate that the Cash Ratio Dr. Soeradji Tirtonegoro hospital after applying the PPK-BLU better than before KDP - BLU. For another study that ratio, Current ratio, Collection Period ,Ffixed asset turnover, Return on assets, Return on equity, Sales Growth ( SALG ) and Growth Activity Dr. Soeradji Tirtonegoro hospital not have a significant difference after applying the PPK-BLU with before PPK-BLU.